Analisis Dan Perancangan Sistem Informasi Manajemen Arsip Berbasis Web Pada Sekretariat DPRD Kota Jambi - Latif, Raden Abdul; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2020)
The DPRD Secretariat has issues relating to archiving files, where the files are difficult to find whenneeded. The DPRD Secretariatstill uses a manual book system to record incoming and outgoing letters.The number of files is increasing everyday, and the manual books system is vulnerable by damaged andvanish, also stand archiving issues of the DPRD Secretariat. This study aims to analyze and design aWeb-based prototype in Archive Management Information System on incoming and outgoing mail,through the Unified Modeling Language (UML)system modeling method. This system is featured tomanage admin data, user data, and archive data, notifying data, managing reports, sending, receiving andarchiving security. The prototype is needed to be develoved and implemented at the Jambi city DPRDSecretariat as a solution to the archiving issues, as well as a step to computerize the archiving DPRDSecretariat.